Multicriteria based priority mapping: charting agroecological pathways in India - Kumar, Gopal; Sikka, Alok; Behera, Abhijit; Malaiappan, Sudharsan (International Water Management Institute, 2024)
The report, titled "Multicriteria-Based Priority Mapping: Charting Agroecological Pathways in India," presents a comprehensive analysis aimed at addressing India’s dual challenges of achieving food security and ensuring environmental sustainability. India, with 18% of the global population and access to only 2.4% of the world’s land and 4% of renewable water resources, faces immense pressure to adopt resource-efficient and sustainable agricultural practices. This study employs a robust multi-criteria decision-making framework, integrating diverse datasets and stakeholder inputs, to guide the prioritization of agroecological interventions.